1990
DOI: 10.1093/ije/19.2.303
|View full text |Cite
|
Sign up to set email alerts
|

Fat Distribution in European Women: A Comparison of Anthropometric Measurements in Relation to Cardiovascular Risk Factors

Abstract: In this study in 437 women born in 1948 selected from five European towns we show that several anthropometric measurements are consistently and significantly associated with a metabolic risk profile in premenopausal women of 38 years of age. Among the circumferences, breast and waist circumference were, after adjustment for body mass index positively correlated with diastolic blood pressure, serum total cholesterol, HDL-cholesterol (negative associations), serum triglycerides, and serum insulin. The optimal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
2
9

Year Published

1994
1994
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 0 publications
5
78
2
9
Order By: Relevance
“…Other methodological differences for measurement of WC, with consequences for WHR, are still prevailing due to lack of adequate standardisation of measurement techniques. In a previous report on 437 European women aged 38 years 34 , measurements of WC at the narrowest circumference were on average 2.7 cm lower than measurements of WC midway between the lower ribs and the iliac crest. No evidence for systemic differences between these methods in middle-aged subjects has been found in the literature, but this methodological inconsistency may affect comparison of WC and WHR data from the different EPIC populations described here.…”
Section: Discussionmentioning
confidence: 63%
“…Other methodological differences for measurement of WC, with consequences for WHR, are still prevailing due to lack of adequate standardisation of measurement techniques. In a previous report on 437 European women aged 38 years 34 , measurements of WC at the narrowest circumference were on average 2.7 cm lower than measurements of WC midway between the lower ribs and the iliac crest. No evidence for systemic differences between these methods in middle-aged subjects has been found in the literature, but this methodological inconsistency may affect comparison of WC and WHR data from the different EPIC populations described here.…”
Section: Discussionmentioning
confidence: 63%
“…Many epidemiologic studies have shown increased visceral fat accumulation to be an independent risk factor for type 2 diabetes mellitus and cardiovascular risk conditions or future events, such as coronary artery disease, stroke and hypertension. 1, [11][12][13] In fact, several anthropometric indices for estimating the abdominal fat distribution, such as waist-tohip ratio, waist circumference and recently, waist-to-height ratio, 5,14 have been regarded as important markers of cardiovascular risk. However, the waist-to-hip ratio may Visceral fat and carotid atherosclerosis SK Kim et al mask the accumulation of abdominal fat, if the hip circumference is also increased.…”
Section: Discussionmentioning
confidence: 99%
“…The waist-to-hip ratio (WHR) was de®ned as the ratio of waist circumference (measured at the level midway between the lateral lower rib margin and the superior anterior iliac crest) divided by hip circumference (measured at the level of the bilateral great trochanters). 26 The whole body composition was obtained directly by the method of dual energy X-ray absorptiometry (DEXA, Lunar radiation Corp, USA, software version 1.3 z). Total body fat percentage was de®ned as a ratio of total body fat massatotal tissue mass.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%